2017
DOI: 10.1177/1062860617732635
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Improvement in Administration of the Hepatitis B Vaccine Birth Dose: A Quality Improvement Initiative

Abstract: The New York State Department of Health recommends the administration of the hepatitis B vaccine birth dose within 12 hours of life (HOL) for all full-term babies irrespective of maternal hepatitis B status. The primary and secondary aims of the project were to improve the timeliness of vaccine administration and increase the total number of infants vaccinated prior to discharge. Multiple Plan-Do-Study-Act cycles were performed. Statistical process charts of percentages of vaccination within 12 HOL and prior t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 8 publications
(9 reference statements)
0
9
0
Order By: Relevance
“…Given these data, strategies to increase administration during hospitalization are needed. Recent quality improvement studies using approaches such as standardization of HepB vaccination processes and greater education of parents, nurses, and providers, markedly improved HepB vaccination of healthy newborns ≥2,000 g before hospital discharge 32 33 ; similar interventions could be considered for these high-risk infants under 2,000 g.…”
Section: Discussionmentioning
confidence: 99%
“…Given these data, strategies to increase administration during hospitalization are needed. Recent quality improvement studies using approaches such as standardization of HepB vaccination processes and greater education of parents, nurses, and providers, markedly improved HepB vaccination of healthy newborns ≥2,000 g before hospital discharge 32 33 ; similar interventions could be considered for these high-risk infants under 2,000 g.…”
Section: Discussionmentioning
confidence: 99%
“…A quality improvement intervention in an urban hospital with high HBV prevalence serving a diverse, largely immigrant and socioeconomically disadvantaged population significantly increased HepB vaccination rates at 12 hours of life with the addition of a standing order for HepB vaccine at birth in addition to physician and nurse education. 13 Contrary to our setting, we had persistent low HepB vaccination rates despite the standing order. The perceived lack of risk of transmission combined with low prevalence was a key barrier to urgency and HepB vaccine receipt before discharge.…”
Section: Discussionmentioning
confidence: 57%
“…Interventions that improve HepB vaccine birth dose rates include standing orders and the codification of a hospital birth dose policy. [11][12][13] Furthermore, enhancements in the vaccine ordering and delivery processes combined with staff education have resulted in improved vaccination rates for birth dose HepB vaccination as well as other vaccines administered in inpatient settings. [13][14][15][16] However, despite national and state recommendations, use of a standing order, and the presence of a hospital birth dose policy, our institutional MBU HepB vaccination birth dose rates were well below national and city averages.…”
mentioning
confidence: 99%
“…Interventions that improved workflow provided additional improvement beyond education alone, similar to findings documented by Nemerofsky et al in their QI efforts to improve timing of the birth dose of hepatitis B vaccine. 7 The improvement in timing of administration has been sustained over a several month period and would be expected to be sustainable long term given that it is based on permanent changes to nursing workflow. Given that our interventions achieved improvements in both a university medical centre and a community hospital nursery setting, we anticipate that other nurseries would be able to use similar interventions to improve rates and timing of vaccine administration.…”
Section: Discussionmentioning
confidence: 99%
“… 6 Nemerofsky et al found most improvement when they addressed workflow by adding the vaccine order to a standard newborn admission order set. 7 Similarly, Madlon-Kay found that a change in the way the vaccine was ordered was associated with an increase in newborns receiving the hepatitis B vaccine prior to nursery discharge. 8 These projects demonstrate how efforts to improve rates and timing of administration of the birth dose of hepatitis B vaccine are amenable to a QI approach to improve care.…”
Section: Introductionmentioning
confidence: 98%